Penerapan Pembelajaran Guided Inquiry untuk Meningkatkan Keaktifan dan Hasil Belajar Siswa SMK Kelas X ATPH - Nuriatus Sholikhah; Fatimah Zahro; Dwi Haryanta (Pragmatik : Jurnal Rumpun Ilmu Bahasa dan Pendidikan, 2025)
Guided inquiry is recognized as an effective instructional model for Vocational High Schools (SMK), as it actively engages students in systematic exploration and investigation with teacher guidance. This study aims to address the problem of low student engagement and learning outcomes by implementing the guided inquiry model in classroom instruction. The research employed a Classroom Action Research (CAR) design, conducted over two cycles, each comprising the stages of planning, action, observation, and reflection.The participants consisted of 36 students from Class X of the Agribusiness for Food Crops and Horticulture (ATPH) program at SMK Negeri 1 Purwosari during the 2024/2025 academic year. Data collection instruments included student engagement observation sheets, evaluation tests, and documentation, with data analyzed using descriptive quantitative methods. The findings revealed that the guided inquiry model significantly improved both student engagement and learning outcomes in the topic of vegetative propagation. Student engagement increased from 32.81% in the pre-cycle to 70.49% in the first cycle and 84.72% in the second cycle. Similarly, the percentage of students achieving mastery in learning outcomes rose from 38.89% in the pre-cycle to 83.33% in the first cycle and reached 100% in the second cycle.